Analysis of Interactive Multimedia Needs in Strengthening Character Responsibility in Pancasila Education Learning in Elementary Schools - Pratiwi, Lia; Wuryandani, Wuri (Jurnal Prima Edukasia, 2025)
This study was motivated by the limitations of innovative learning media in internalizing students' character of responsibility in Pancasila education learning in elementary schools. The purpose of this study was to analyze the need for interactive multimedia as a supporting medium for strengthening the character of responsibility. The research employed a descriptive qualitative method, with data collected through questionnaires, semi-structured interviews, and observations. The data were analyzed descriptively, using triangulation to enhance validity. The research subjects comprised 157 fourth-grade students and 10 teachers from elementary schools in the Kemantren Kraton area of Yogyakarta City. The results of the study indicate that students' sense of responsibility remains low, teacher-parent collaboration is not yet optimal, and there is a strong need for effective, contextually relevant interactive multimedia. These findings emphasize the need to develop interactive multimedia that not only supports the understanding of Pancasila Education material but also optimally strengthens the formation of character of responsibility in elementary school students.